(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Survey the rate of stress, depression, and anxiety of patients before planned surgery at the University Medical Center Ho Chi Minh city branch 2. Methods: Cross-sectional description of 205 patients scheduled for planned surgery at the Department of Anesthesia and Resuscitation, University Medical Center Ho Chi Minh city branch 2. Results: The rate of patients in the ≤ 60 years old group accounted for 81.95%, the rate of patients in the > 60 years old group accounted for 18.05%. The rate of patients participating in the study who were female (55.61%) was higher than that of male (44.39%). The rate of stress, depression, and anxiety of patients before planned surgery at the University Medical Center Ho Chi Minh city branch 2 was 4.39%, 5.858%, and 24.39%, respectively. Conclusions: The rates of stress, depression, and anxiety in patients before planned surgery at University Medical Center Ho Chi Minh city branch 2 were 4.39%, 5.858%, and 24.39%, respectively.